Integration of Safety Management System with other systems in Aircraft Maintenance Services Companies in Indonesia - Rosita, Ai; Rahayu, Agus; Adi Wibowo, Lili (International Journal of Psychosocial Rehabilitation, 2020)
One of the determinants of the advancement of the aviation industry is the support of aircraft maintenance companies, or aircraft maintenance and overhaul (MRO). The airlines are very hopeful of MRO facilities in order to extend the life of the company’s assets to ensure the availability of transportation services in the future. MRO services are very complex because they involve various processes whose performance depends on aircraft buildup and maintenance reliability, regulations, spare parts availability, and availability of certified human resources (Vieira & Loures, 2016). The number of incidents of civil aviation accidents is the biggest issue for the entire world community, both national and international flights. There are four main parts of the organization that are operational actors in the aviation world: aircraft operator company, air traffic control organization, airport operations, and aviation operations (Aviation & Regulation, n.d.). The implementation process of applying SMS to MRO companies was built with four main pillars, namely: safety policy, safety risk management, safety assurance, and safety promotion media. The safety policy covers the concentration and commitment of the company’s leadership to the implementation of the Safety Management System in an MRO, especially regarding the resources that must be provided by the leadership. Safety risk management includes monitoring of all ten potential hazards with conditions below the acceptable risk threshold. Safety assurance is a safety guarantee that is demonstrated by maintaining all potential hazards below the permitted value threshold. Safety promotion is an activity carried out continuously by the company to enhance the safety awareness of all company employees.